Deduction of Crime in the Urban Matrix: A Comparative Analysis between Kiriti Roy and Sherlock HolmesIntroduction (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Detective fiction, as a literary genre, provides a compelling lens to examine the interplay of crime, society, and urban spaces. This study offers a comparative analysis of two iconic literary detectives—Sherlock Holmes, the emblematic figure of Victorian London created by Sir Arthur Conan Doyle, and Kiriti Roy, a prominent Bengali detective crafted by Nihar Ranjan Gupta. While both characters employ deductive reasoning and psychological insight, their investigative methods, ethical frameworks, and engagements with urban environments reflect distinct cultural and historical contexts. Holmes’ approach, rooted in scientific empiricism and forensic observation, epitomizes the rationalist ethos of late 19th- and early 20th-century Britain, transforming the complexities of London into a structured and decipherable space. In contrast, Kiriti Roy’s deductive practices are intertwined with Indian sociopolitical realities, moral philosophies, and humanistic empathy, offering nuanced reflections on postcolonial Kolkata with its layered urbanity, class tensions, and colonial legacies. This research examines how urban settings act as active agents in shaping crime narratives, influencing the detectives’ methods, narrative perspectives, and problem-solving strategies. By analyzing deductive methodologies, character development, and interactions with law enforcement, the study identifies both convergences and divergences between Western and South Asian detective traditions. Furthermore, it situates these findings within broader discussions of postcolonial literary studies, urban semiotics, and cross-cultural crime fiction scholarship. Ultimately, the study underscores the importance of examining regional literary figures like Kiriti Roy alongside globally celebrated detectives, highlighting the culturally specific and universal aspects of crime deduction. This comparative framework enhances understanding of how literature mediates perceptions of logic, justice, and urban complexity, offering insights valuable for literary criticism, urban studies, and pedagogy.